Stigma and discrimination of Indian women living with HIV/AIDS : perceptions and experiences of women in Mumbai, India - O'Connor, Pamela Margaret (Curtin University, 2008)
Stigma and discrimination are now recognised as major factors in the spread of Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS). To date, research has focused on how to change individual responses to stigma and discrimination without exploring the social and structural dimensions. Complex community and societal dimensions, such as culture, power and difference need to be explored if progress is to be made in coping with stigma and discrimination. India now has HIV/AIDS prevalence figures to rival sub Saharan Africa. The disease has spread from high-risk populations such as intravenous drug users and commercial sex workers into the general population. Married, monogamous, heterosexual women in slum communities are highly vulnerable. Factors such as caste, class, ethnic group, poverty and social expectations present formidable layers of stigma for these women. They have also faced discrimination since before their birth. HIV/AIDS imposes yet another layer of stigma and discrimination upon their shoulders. The aims of the study were firstly to investigate whether stigma and discrimination existed for these women by documenting and analysing literature on the individual, societal and cultural situation of Indian women living with HIV/AIDS (IWLWHAs). Secondly, the study aimed to identify, evaluate and explore the psychosocial needs and coping strategies of IWLWHAs, to determine the barriers to accessing health services, and describe community perceptions as they were experienced by the participants.This qualitative research study examined the multiple layers of stigma and discrimination experienced by women infected and affected by HIV/AIDS in a low socio-economic area of Mumbai, India. This was achieved by interviewing women who were benefiting from a home-based service - Positive Living - An integrated home-based care programme for people living with HIV/AIDS under the auspices of the KJ Somaiya Hospital in Mumbai. This programme provides a nutrition and home-based service to the nearby community slums. The conceptual framework used for this study was developed to evaluate the effects of natural disasters such as tsunamis, floods and earthquakes. HIV/AIDS is no less of a tragedy for individuals, families and communities. Within this framework, human capacity or the ability of individuals to cope is linked to social ecology - the relationship between individuals and their community. This dimension overlaps with culture and values. Three other dimensions affect humans - economic status, the environment and living conditions, and physical health. I have developed this framework further to examine threats and strengths which arise from these dimensions, and which affect human resilience. An exploratory case study was considered the most suitable approach to explore these areas, as it permits more sensitivity and richer data, and enhances rigour. In-depth interviews of 45 women in three different age groups, home visits and observations, focus group discussion, key informants, narratives, vignettes and photographs were supported by documentary data collection in triangulation of the data. A reflective journal recorded observations and perceptions in the field during three months in India.Results from the combined data indicated that IWLWHAs experienced discrimination in their families, communities and health care settings. Fear of future discrimination ensured secrecy which, in turn, prevented them accessing community services which would provide emotional and physical support. A range of reactions was demonstrated by the affected women, half of whom were also infected which added to their burden. Women who could not disclose their condition were extremely isolated, lacked family and community support, feared the future and felt hopeless. Despite their appalling living conditions of poverty, overcrowding, prevalence of disease and pollution, the women displayed a sense of pride, dignity and resilience. Culturally appropriate strategies are necessary to address the lack of education and awareness as only two of the 45 women had any knowledge of HIV/AIDS before their own diagnosis which often followed their husbands' positive status. In addition, the social and cultural dimensions which affect these women have to be explored and examined in order to strengthen the 'shock absorbers' of the family. The community health workers and co-ordinator of the home-based service were vital in providing emotional support and health information to the women. Finally, no change is possible unless men take responsibility for their sexual mores. Policy makers and programmes have to look further for strategies which would engage men in the process to change their attitudes and thus protect vulnerable women and children.